Ekowisata Air Terjun Cunca Rami Dalam Bingkai Partisipasi Masyarakat Desa Golo Ndaring Kabupaten Manggarai Barat - Muen, Lydia; Pujaastawa, Ida Bagus Gde; Sudiarna, I Gusti Putu (Sunari Penjor : Journal of Anthropology, 2021)
Cunca Rami is one of the interesting tourist destinations that are currently getting the attention of the local government. The purpose of this study was to analyze the participation of the people of Golo Ndaring Village in the Development of Ecotourism in Cunca Rami Waterfall. The formulation of the problems in this study include (1) How Community Participation in the Development of Ecotourism Cunca Rami Waterfall; (2) What factors influence community participation in the development of Cunca Rami Waterfall Ecotourism; (3) What are the implications of community participation in the development of Cunca Rami Waterfall Ecotourism.This research uses participation theory and tourism impact theory. The analysis used is descriptive qualitative. The research was conducted using the participatory observation method, the writer as a researcher lives in the context of his community. The author also participates in community activities carried out by local residents. Data collection was carried out by in-depth interview method in order to obtain actual data. The results of the study concluded that there was the participation and involvement of the village community of Golo Ndaring in the development of Cunca Rami Waterfall Ecotourism. This community participation is influenced by the increasing popularity of the Waterfall, regional tourism development policies and economic motivation. The implications for community participation include: economic implications, socio-cultural implications, and environmental implications.